Effect of farmer group membership on agricultural technology adoption and crop productivity in Uganda - Mwaura, F. (African crop science journal, 2014)
The deteriorating agricultural performance over the past decade that coincided with the duration of targeting farmer groups as the sole public supported extension approach in Uganda, calls for intervention on agricultural information dissemination. Uganda Census of Agriculture database of 2008 - 2009 was used to evaluate the effect of farmer group membership on agricultural technology adoption and crop productivity. This particular study aimed at providing policy; answers to whether the use of farmer’ groups approach in agricultural information dissemination is resulting in increased adoption of technologies and improved yields. Descriptive statistics and results of translog production function, and propensity score matching were used to provide insights into household major characteristics and to assess the impacts of group membership on adoption of technology and agricultural productivity. Membership to farmer groups in Uganda is low. Only 16 percent of household heads belonged to a group. Although membership to groups resulted in increased yields for banana and cassava, negative impacts were observed for sweet potatoes, beans and maize. Group members were less likely to adopt inorganic fertilisers (P<0.01) and improved seed (P<0.05) than non-groups members. Although not significant (P<0.05), group members’ achievement of yields of 3 and 2 t ha-1, respectively, for banana and cassava than nongroup members is quite high and of interest for development agencies. On the other hand, non group members’ sweet potato yields were 1.0 tonne per hectare, higher than group’s members although not significant (P>0.05)